Systematic Literature Review: Digitalization of Rural Tourism Towards Sustainable Tourism - Rasyidah; Erianda, Aldo; Alanda, Alde; Hidayat, Rahmat (SOTVI, 2023)
In the context of rural tourism, the internet is crucial. It is vital to create and implement new technology in order to assist digital tourism in tourist communities and undeveloped, frontier, and remote locations. The utilization of big data can enhance the precision of predicting tourist flows, providing valuable insights to assist and enhance destination management, planning, and advertising. It can also ease mobility and encourage visitors to be distributed according to time. In addition to supporting visitors with specific access needs and keeping management informed about visitor behavior, artificial intelligence (AI) and automation can also be very helpful in the tourist industry by enabling those with limited mobility to travel the world. In this sense, as the sharing and gig economies grow along with technology, we have more options in our everyday lives—as long as they are properly set up and maintained. Therefore, this paper aims to study the research on internet criteria based on AlUla framework to achieve sustainable tourism in rural areas and to identify the key journals, articles and authors. The findings in this research are that there has been an increase in the number of journals post COVID19, where the country that produces the most journals is China and the author that is most cited is Pesonen JA. To achieve the goal of sustainable digital rural tourism, infrastructure is needed in the form of internet penetration, internet speed and usability, and internet security level.